#### Answer

$gā(x) = 2x^2 + 2- \frac{6}{x^3} $

#### Work Step by Step

$g(x) = \frac{(x^3+2x^2+\frac{3}{x})}{x} $
Simplify:
$g(x) = x^2 +2x+\frac{3}{x^2} $
Power Rule:
$gā(x) = 2x^2 + 2- \frac{6}{x^3} $

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

$gā(x) = 2x^2 + 2- \frac{6}{x^3} $

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.